Adsorption of Nitrate from Water by Zn-Al Layered Double Hydroxide - Hamieda Eadan Salman (Journal of Global Pharma Technology, 2018)
Zinc-aluminum Layered double hydroxide was synthesized by copercipitation method in molar ratio Zn/Al 4:1.The prepared layered double hydroxide were characterized by Fourer-transform infrared spectra (FTIR),X-ray diffraction (XRD)and Atomic force microscope (AFM).The synthesized layered double hydroxides were used to study the adsorption of nitrate anion (NO3-) from water. The influence of some parameters on nitrate adsorption, including PH, temperature and adsorption of kinetics the results showed that the adsorption of nitrate anion (NO3-) on the surface of the layers (Zn/Al-LDH) increases by increasing the temperature but decreases by increasing the PH and the adsorption of isotherm is following the frindlch equation .The adsorption of kinetics were subjected to modified first grad false the lagergren equation. The thermodynamic parameters, such as (∆H, ∆G, ∆ S) clarified that the adsorption on the Zn/Al-LDH is endothermic and spontaneous.Keywords: Layered double hydroxide, Adsorption, Nitrate.